From temporariness to mobility futures: A review of progress in tactical urbanism as an active travel planning tool - Jarvis Suslowicz; Helge Hillnhütter (Transportation Research Interdisciplinary Perspectives)
This article explores progress in institutional efforts to use tactical urbanism as planning tool for driving a modal shift towards active travel in urban areas. Using a tried and tested framework for assessing transitional capacity of street experiments, this article reviews 92 semi-systematically selected academic works, most covering a range of temporary street-space reallocation projects linked by a common purpose of supporting a shift to active travel modes. It confirms that although tactical urbanism is now widely used to carve out space for walking and cycling, particularly with the opportunity presented by the COVID-19 pandemic, most projects still encounter difficulty in transitioning towards later-stage outcomes, with common blockages appearing throughout: (1) the temporariness of funding schemes and networks of governance; (2) deficient strategic foresight into the transition towards a long-term vision for mobility; (3) inadequate engagement with both supporters and critics of change; and (4) inattention to network principles of urban mobility otherwise considered in their permanent counterparts. Though critical, the review highlights cases which viably use tactical urbanism as a step towards long-term, large-scale change, with weaknesses presented as focal points for awareness by practitioners hoping to utilise tactical urbanism for this purpose.